Genome and transcriptome-wide study of carbamoyltransferase genes in major fleshy fruits: A multi-omics study of evolution and functional significance - Dhar, Yogeshwar V.; Asif, Mehar H. (Frontiers in Plant Science, 2022)
The carbamoyltransferase or aspartate carbamoyltransferase (ATCase)/ornithine carbamoyltransferase (OTCase) is an evolutionary conserved protein family, which contains two genes, ATCase and OTCase. The ATCase catalyzes the committed step in the synthesis of UMP from which all pyrimidine molecules are synthesized. The second member, OTCase, catalytically regulates the conversion of ornithine to citrulline. This study traces the evolution of the carbomoyltransferase genes in the plant kingdom and their role during fruit ripening in fleshy fruits. These genes are highly conserved throughout the plant kingdom and, except for melon and watermelon, do not show gene expansion in major fleshy fruits. In this study, 393 carbamoyltransferase genes were identified in the plant kingdom, including 30 fleshy fruit representatives. Their detailed phylogeny, evolutionary patterns with their expression during the process of fruit ripening, was analyzed. The ATcase and OTcase genes were conserved throughout the plant kingdom and exhibited lineage-specific signatures. The expression analysis of the ATcase and OTcase genes during fruit development and ripening in climacteric and non-climacteric fruits showed their involvement in fruit ripening irrespective of the type of fruits. No direct role in relation to ethylene-dependent or -independent ripening was identified; however, the co-expression network suggests their involvement in the various ripening processes.